Influence of Joint Dip Angle on Dynamic Mechanical Properties and Crack Propagation Law of Rock-like Materials. Issue 4 (October 2021) - Li, Xiaoshuai; Guo, Lianjun; Gao, Wenxue
Abstract: The main objective of this study is to investigate the dynamic mechanical properties and crack propagation law of rock-like materials with different joint dip angles. The precast cement mortar specimens are impacted by split Hopkinson pressure bar (SHPB). The meso damage of the specimens before and after impact is detected by nuclear magnetic resonance system (NMR), and the crack propagation path is extracted. The influence of joint dip angles on dynamic response characteristics of rock-like materials is analyzed from the aspects of dynamic compressive strength, meso damage and crack propagation path. The analysis indicates that joints make the internal stress distribution of rock-like materials uneven, resulting in the weakening of the dynamic compressive strength of rock-like materials. At the same time, joint characteristics affect the weakening degree of the dynamic compressive strength of rock-like materials. With the increase of joint dip angle, the weakening degree of dynamic compressive strength of rock like materials first increases and then decreases. The relationship between the damage degree and the dynamic compressive strength of rock-like materials is approximately negative linear. With the increase of joint dip angle, the damage degree changes in an inverted "U" shape. Tensile stress or the combination of tensile stress and shear stress leads to the initiation and propagation of cracks. The intact specimens, the specimens with joint dip angle of 0°, and the specimens with joint dip angle of 90° develop axial tensile cracks. The specimens with joint dip angles of 15°-75° develop tensile cracks and shear cracks at the joint tips.